Potential mechanism of enhanced postprandial glucagon‐like peptide‐1 release following treatment with a diacylglycerol acyltransferase 1 inhibitor. Issue 6 (30th November 2015) - Liu, Jinqi; McLaren, David G.; Chen, Dunlu; Kan, Yanqing; Stout, Steven J.; Shen, Xiaolan; Murphy, Beth Ann; Forrest, Gail; Karanam, Bindhu; Sonatore, Lisa; He, Shuwen; Roddy, Thomas P.; et al.
Abstract: Studies have demonstrated that blockade of diacylglycerol acyltransferase 1 (DGAT1) leads to prolonged release of glucagon‐like peptide 1 (GLP‐1) after meal challenge. The current study was undertaken to investigate the mechanism of action underlying the elevated levels of GLP‐1 release following pharmacological inhibition of DGAT1. We utilized a potent, specific DGAT1 inhibitor, compoundA, to investigate the changes in intestinal lipid profile in a mouse model after oral administration of the compound and challenge with tracer containing fatty meal. [ 13 C18 ]‐oleic acid and LC‐MS were employed to trace the fate of dietary fatty acids provided as part of a meal challenge in lean mice. Lipid profiles in plasma, proximal to distal segments of intestine, and feces were evaluated at various times following the meal challenge to study the kinetics of fatty acid absorption, synthesis into complex lipids, and excretion. Pharmacological inhibition of DGAT1 led to reduction of postprandial total and newly synthesized triglyceride (TG) excursion and significant increases in TG and FFA levels in the distal portion of intestine enriched with enteroendocrine L cells. Enhanced levels of FFA and cholesteryl ester were observed via fecal fat profiling. DGAT1 inhibition leads to enhancement of carbon flow to the synthesis of phosphatidylcholine within the intestine. DGAT1 inhibition markedly increases levels of TG and FFA in the distal intestine, which could be the predominant contributor to the prolonged and enhanced postprandial GLP‐1 release. Inactivation of DGAT1 could provide potential benefit in the treatment of dysmetabolic diseases.